MyD88 Is Required for Efficient Control of Coxiella burnetii Infection and Dissemination - Kohl, Lisa; Hayek, Inaya; Daniel, Christoph; Schulze-Lührmann, Jan; Bodendorfer, Barbara; Lührmann, Anja; Lang, Roland (Frontiers in Immunology, 2019)
The intracellular pathogen Coxiella (C.) burnetii causes Q fever, a usually self-limiting respiratory infection that becomes chronic and severe in some patients. Innate immune recognition of C. burnetii and its role in the decision between resolution and chronicity is not understood well. However, TLR2 is important for the response to C. burnetii in mice, and genetic polymorphisms in MyD88 have been associated with chronic Q fever in humans. Here, we have employed MyD88-deficient mice in infection models with the attenuated C. burnetii Nine Mile phase II strain (NMII). MyD88-/- macrophages failed to restrict the growth of NMII in vitro, and to upregulate production of the cytokines TNF, IL-6 and IL-10. Following intraperitoneal infection, NMII bacterial burden was significantly higher on day 5 and 20 in organs of MyD88-/- mice. After infection via the natural route by intratracheal injection, a higher bacterial load in the lung and increased dissemination of NMII to other organs was observed in MyD88-deficient mice. While wild-type mice essentially cleared NMII on day 27 after intratracheal infection, it was still readily detectable on day 42 in multiple organs in the absence of MyD88. Despite the elevated bacterial load, MyD88-/- mice had less granulomatous inflammation and expressed significantly lower levels of chemoattractants, inflammatory cytokines, and of several IFN-induced genes relevant for control of intracellular pathogens. Together, our results show that MyD88-dependent signaling is essential for early control of C. burnetii replication and to prevent systemic spreading. The continued presence of NMII in the organs of MyD88-/- mice constitutes a new mouse model to study determinants of chronicity and resolution in Q fever.